Business Innovation : a case study approach - Pandiarajan, Vijay (London: New York: Routledge, Taylor and Francis, 2022)
"This book takes a holistic approach to enterprise and innovation opportunities and challenges by addressing the key questions surrounding innovation - what, why, and how. It provides an understanding of innovation models and why they are important in the business context, considers sources of innovation, and how to apply business frameworks using real world examples of innovation-led businesses. After providing a solid background to the key concepts related to innovation models, the book looks at why innovation takes place and where the sources of innovation lie, from corporate research to crowd-sourced and government-funded initiatives. Innovation models across manufacturing, services and government are explored, as well as measuring innovation, and the impact of design thinking and lean enterprise principles on innovation and sustainability-driven imperatives. Real-life, global case studies are integrated throughout to demonstrate how the concepts can be applied to practice, supported by a new 5-dimensional holistic framework for innovation. Chapter objectives and summaries, key learning points and questions reinforce learning and aid critical thinking. Offering a truly comprehensive and global approach, Business Innovation should be core or recommended reading for advanced undergraduate, postgraduate, MBA and Executive Education students studying Innovation Management, Strategic Management and Entrepreneurship. Supporting materials include PowerPoint slides, a test bank of questions and an instructor's manual"--
Includes bibliographical references and index.
Keywords: Business enterprises -- Technological innovations; Technological innovations -- Management; Business planning